Territory and struggle for rights from Morro da Piedade, in Vitória (ES) (PerCursos, 2023)
Morro da Piedade is located in Vitória (ES), Brazil, and has been experiencing a process of resident evasion since 2018, due to the dispute over territory between groups linked to drug trafficking. In this context, movements and collectives emerged that articulate and question the relationship between the State and the territory. This article aims to analyze the attempts to redefine space, which took place between 2018 and 2021. The theoretical-methodological framework adopted is that of Marxist critical theory. The research instruments are case study, participant observation, interviews, data analysis and literature review.
Keywords: territory; urban violence; deterritorialization; fight for rights; right to the city